THE INFLUENCE OF INTELECTUAL CAPITAL AND ISLAMICITY PERFORMANCE INDEX ON FINANCIAL PERFORMANCE IN SHARIA BANKING IN INDONESIA - Marzuki, Marzuki; Akhyar, Chairil; Nazir, Nazir (RADJA PUBLIKA, 2022)
This research was conducted with the aim of examining the effect of intellectual capital and the Islamic performance index on the financial performance of Islamic banking in Indonesia. The data used in this research is documentation data as much as 110 data which is the result of multiplication of 11 object observation data with 10 years observation period of Islamic banking financial reports for the period 2010-2019. This study uses the Moderation Regression Analysis research method with a static panel approach. The results of the data analysis found that the intellectual capital variable which is proxied by VACA, VAHU, STVA has a significant effect on financial performance. Furthermore, the Islamic Performance Index variable which is proxied by PSR, ZPR, EDR, and IsRI has a positive and significant effect on the financial performance of Islamic banking in Indonesia. Another finding found that the variable company age did not moderate intellectual capital (VAIC) on financial performance, while firm size moderated intellectual capital on financial performance. Based on these findings, it is hoped that the leadership of Islamic banking in order to improve the financial performance of Islamic banking needs to increase the Intellectual Capital and Islamicity Performance Index.